Answer:
[tex]U = x[/tex]
[tex]V=10[/tex]
Step-by-step explanation:
Given
[tex](x +3)^2 + 14(x + 3) + 49 = (U + V)^2[/tex]
Required
Find U and V
We have:
[tex](x +3)^2 + 14(x + 3) + 49 = (U + V)^2[/tex]
Expand
[tex]x^2 + 6x + 9 + 14x + 42 + 49 = (U + V)^2[/tex]
Collect like terms
[tex]x^2 + 6x + 14x + 9 + 42 + 49 = (U + V)^2[/tex]
[tex]x^2 + 20x + 100 = (U + V)^2[/tex]
Expand
[tex]x^2 + 10x + 10x + 100 = (U + V)^2[/tex]
Group
[tex][x^2 + 10x] + [10x + 100] = (U + V)^2[/tex]
Factorize each group
[tex]x[x + 10] + 10[x + 10] = (U + V)^2[/tex]
Factor out x + 10
[tex][x + 10][x + 10] = (U + V)^2[/tex]
So, we have:
[tex][x + 10]^2 = (U + V)^2[/tex]
By comparison
[tex]U = x[/tex]
[tex]V=10[/tex]